SINERGI MASYARAKAT DALAM PENGEMBANGAN USAHA PRODUKSI DAN PENJUALAN KUE KELOMPOK WANITA TANI DESA SUMBER AGUNG - PRAMUKA, PPK ORMAWA (SINAR SANG SURYA, 2025)
The Kelompok Wanita Tani (KWT) in Sumber Agung Village, Batanghari Subdistrict, East Lampung, has been mentored by Universitas Muhammadiyah Metro through the Pramuka Student Activity Unit since 2021. KWT manages five ventures, including cake production, grape seedling cultivation, and internet reselling. However, between 2022 and 2024, KWT faced various challenges, such as unstable internet access and the failure of the grape crops. Despite this, cake production continued, and the grape fields were converted into vegetable gardens. Through the Wiradesa Kemendikbud program, sustainable mentorship was provided to improve KWT's capacity, including entrepreneurship training, digital marketing, and the use of modern tools. The program successfully supported 14 households and expanded its reach to Banjarrejo and Tejosari. KWT also serves as a cake supplier at Tejo Agung market and provides training to 50 mobile vegetable vendors. Government and university support have contributed to the development of this initiative. The solutions offered include equipment assistance, packaging training, and digital marketing strategies. This program has increased production capacity, sales, and community participation, although challenges remain in stabilizing income. The program's sustainability potential is high due to strong support from the government, the university, and local distributors.